Pengaruh Konsentrasi HCL Dan Deterjen Terhadap Fluks Dan Resistance Removal Untuk Pencucian Kimia Membran Ultrafiltrasi Pada Pengolahan Limbah Cair Tahu - Romfis, Dio; Syarfie, Syarfie; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
One of the challenges / constraints of the use of membrane technology in the filtration system is fouling. This research aims to determine the effect of the concentration of HCl and detergent removal in flux and resistance affect the performance of ultrafiltration membranes. This research uses the membrane system to cross flow with varying operating pressure of 0.2 bar, 0.4 bar and 0.6 bar, the variation in concentrations of HCl and detergent 1.5%, 2% and 2.5%. The screening process liquid waste out for 120 minutes and each time washing to obtain HCl approximately 60 minutes and detergents lasted 30 minutes. The highest level of effectiveness laundering obtained 67.63% use traditional detergents 2.5%, the highest washing efficiency is based on the value of flux recovery by 85.55% and 67.62% removal resistance value. The highest flux value after chemical leaching is 0.3896 ml / menit.cm2 at an operating pressure of 0.6 bar membrane and chemical concentration of detergent 2%.Key word : flux recovery, membrane ultrafiltration,resistance removal